Evaluating Technological Innovation of Media Companies from the Perspective of Technological Ecosystem. (10th December 2021) - Yi, Kui; Zhang, Ligang; Mao, Xiulan; Li, Yi; Bao, Jiaxuan
Abstract : The evaluating indicators on the benefits of innovative technology to media companies are preliminarily analyzed and evaluated, according to the research review and evaluating criteria of self-organization and ecosystem selection. Factor analysis and structural equation modeling are used to further explore and select the indicators. According to the results, from the perspective of technology ecosystem, innovative technology performance of media companies can be measured through a two-factor structure—the input of innovative technology and its output. On this basis, ANP (analytic network process) is used to establish a weighted evaluation of indicators. At the end of the paper, a complete set of evaluation systems was created to measure the performance of technology innovation.